Characterization of perineural invasion in different histological grades and variants of oral squamous cell carcinoma - Deepthi, G (J Oral Maxillofac Pathol, 2020)
BACKGROUND: Oral squamous cell carcinoma (OSCC) accounts for 3% of all malignant neoplasms and is the fifth most frequent cancer in the world. They usually spread by hematogenous or lymphatic spread, and perineural invasion (PNI) is considered an alternate method of tumor spread where it is described as the tumor affinity toward a neural tissue. AIM AND OBJECTIVES: The present study aims to evaluate the biological behavior of OSCC with respect to PNI and to evaluate the importance of PNI with respect to different histopathological grades and variants, tumor stage and lymph node status of OSCC. PNI was also assessed with respect to its frequency, patterns, types and number in various grades of OSCC. MATERIALS AND METHODS: This retrospective, double-blind study was conducted on 148 histopathologically proven cases of different histopathological grades and variants of OSCC. The tissue sections were examined for PNI and its patterns and were further compared with habit history, site of the lesion, tumor staging, grading and lymph node status. RESULTS: A Chi-square test was performed. A percentage positivity of 45.27% (67 cases) among 148 cases was found. PNI positivity of 63.6% and 50% was observed in T4 and T3 tumor stages, respectively, with high significance. Seventy percent of cases belonging to poorly differentiated squamous cell carcinoma showed positivity for PNI, which was statistically significant. PNI positivity with respect to lymph node status is nonsignificant. CONCLUSION: The present study showed that there is a direct proportionality between PNI and different grades and stages of OSCC. Given this context, a histopathologist ought to examine for PNI and make it mandatory to report the same to the clinician for better treatment and follow-up of the patient.